Behaviors of steel-plate and concrete in steel-concrete-steel panels subjected to biaxial tension-compression. (April 2021) - Huang, Cheng-Jun; Wu, Xiao-Ang; Chen, Si-Jia; Song, Xiao-Bing
Graphical abstract: Abstract: With the increasing application of steel–concrete-steel (SCS) composite structures in engineering constructions, the mechanical behaviors of steel plates and concrete in SCS structures are becoming increasingly important. This study aimed to evaluate the individual smeared behaviors of the steel plate and concrete from some tested SCS panels and analyze the main characteristics of the plates and concrete. An incremental step analysis method was used to analyze prior experimental research, in which seven SCS panels were subjected to proportional biaxial tension–compression loading. This method is based on Navier's three principles (stress equilibrium, strain compatibility, and the constitutive laws of materials). Using this method, the smeared behaviors of the steel plates and concrete were evaluated. Through analysis, it was found that these smeared behaviors exhibit the following characteristics: When plastic flow occurs, the smeared stress state of steel plates flows on the yield surface after yielding, which results in an increasing principal tensile stress and a decreasing principal compressive stress. For the concrete in the principal compressive direction of the SCS panels, confinement and softening effects may coexist. The concrete in the principal tensile direction of the SCS panels exhibits two different behaviors, and an unexpected compressive stress may be generated. These findings will provide a clearer understanding of the mechanical behaviors of concrete and steel plates in SCS panels in future research.